DIFFUSION OF A CONTAMINANT WITH INHOMOGENEOUS BOUNDARY CONDITIONS - Santiago Ayala, Yolanda Silvia (2005)
We prove the existence of solution for a mathematic model of diffusion of a contaminant using the Nonlinear Semigroups Theory, by means of afin operators. We also study a realistic model by means of satura tíon effects.